Investor reaction on value added tax incentives during COVID-19 - Tatemba, Happy; Morasa, Jenny; Budiarso, Novi Swandari (The Contrarian : Finance, Accounting, and Business Research, 2024)
The COVID-19 pandemic is one of the causes of the weakening of the world economy. Anticipating these conditions, the Indonesian Government implemented several fiscal policies, one of which was the VAT incentive. The aim of this study is to examine the impact of this policy on the capital market. The sample from this study is listed firms in the property sector with an observation period of 2020 to 2022. The findings show that this policy effectively causes the market to become more efficient except during the second phase of implementation. Other findings also show that the implementation of VAT incentives can increase market risk in the property sector. This study also found that the implementation of the VAT incentive policy only had a small impact so that it did not provide a significant difference in returns except during the second phase of the implementation period.